Exploring young consumers’ purchase intention towards foreign brand / Etty Harniza Harun...[et al.] - Harun, Etty Harniza; Abdullah, Nor Hidayah (Universiti Teknologi MARA, Kedah, 2011)
This study was conducted with the purpose of understanding young consumers’ preference towards foreign brands in contrast to local brands. A total sample size of 300 respondents has been distributed to undergraduate students in UiTM Kedah with the purpose of understanding and identifying whether perceived quality, prestige, value and influence from others have relation with purchase intention on Malaysian young consumers towards foreign products. Two items were used as the dependent variable (purchase intention) to test the relationship between variables stated that is personal care products and personal apparel products. The data obtained from the survey were analyzed using SPSS version 16. The result from this study indicated that the young generations are more prone towards buying foreign brand products rather than local brand products as their final consumption. The result obtained from this study is beneficial as a direction for local marketers in understanding what the criteria are searched by local consumers in buying consumer items and what can be done by them in improving the products offered.